MENAKAR RASA KEADILAN PADA PUTUSAN HAKIM PERDATA TERHADAP PIHAK KETIGA YANG BUKAN PIHAK BERDASARKAN PERSPEKTIF NEGARA HUKUM PANCASILA - Hakim, Abdul (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2017)
Law is a set of words that are systematically linking an authoritative text, according to Gustav Radbruch, it should contain three (3) elements, namely fairness, certainty and expediency. The application of the authoritative text in social life was an absolute authority of a judge in resolving a civil case. The judge, in the checking-hearing-deciding a case, not only expected to return the case to the original state (restitutio in integrum) before the advent of the dispute, but should attempt made every effort to not create new disputes or disputes derived from the subject matter examined. Therefore, it becomes very important role of the paradigm for a judge in deciding the case in order to fulfill a sense of justice. Therefore, deciding the case in a precise sense of justice will be a judge most important role. Nowadays, the meaning of